2006
DOI: 10.1128/aem.01184-06
|View full text |Cite
|
Sign up to set email alerts
|

Assay of Poly(3-Hydroxybutyrate) Depolymerase Activity and Product Determination

Abstract: Two methods for accurate poly(3-hydroxybutyrate) (PHB) depolymerase activity determination and quantitative and qualitative hydrolysis product determination are described. The first method is based on online determination of NaOH consumption rates necessary to neutralize 3-hydroxybutyric acid (3HB) and/or 3HB oligomers produced during the hydrolysis reaction and requires a pH-stat apparatus equipped with a softwarecontrolled microliter pump for rapid and accurate titration. The method is universally suitable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 62 publications
2
52
0
2
Order By: Relevance
“…The bacterial strains and plasmids used in this study are listed in Table 1. R. eutropha was grown in nutrient broth (NB) or mineral salts medium with sodium gluconate (or fructose) as described previously at 30°C (1,5). Escherichia coli strains were maintained in Luria-Bertani broth (37°C).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial strains and plasmids used in this study are listed in Table 1. R. eutropha was grown in nutrient broth (NB) or mineral salts medium with sodium gluconate (or fructose) as described previously at 30°C (1,5). Escherichia coli strains were maintained in Luria-Bertani broth (37°C).…”
Section: Methodsmentioning
confidence: 99%
“…nPHB granules were isolated from French presslysed cells (in the presence of 1 mM dithiothreitol [DTT]) by two glycerol gradient centrifugations as described previously (5,12,23). Cholate-coated artificial PHB (aPHB) granules were prepared as described elsewhere (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the gene coding for the iPHA MCL depolymerase (phaZ) is located between two copies of PHA MCL synthase genes (phaC1 and phaC2) in all investigated PHA MCLaccumulating bacteria. Recently, iPHA depolymerase activity could be demonstrated in vitro by use of radiolabeled substrates (nPHA MCL ) or by pH stat (nPHA SCL ), respectively (5,16). iPHB depolymerases of PHA SCL -accumulating bacteria were not described before 2000, but in the first 5 years of this century no fewer than seven putative iPHB depolymerases and two 3HB oligomer hydrolases have been postulated for R. eutropha (1, 23, 44-46, 71, 88, 123).…”
Section: Ipha Depolymerasesmentioning
confidence: 99%
“…The first degradation assays carried out with such isolated nPHB granules revealed the release of 3-hydroxybutyrate (3HB) in a hydrolytic reaction, although only small amounts could be detected (47). In contradiction to that study, the same laboratory revealed in 2007 a thiolytic activity of the PHB depolymerase PhaZ1.…”
mentioning
confidence: 87%